The levels of scientific understanding and attitude towards science among primary school science teachers in the Kuching District of Sarawak - Shirini Mastura, Binti Mohamed Zulkifli. (1998)
The aim of this study was to ascertain the level of scientific understandings of primary school science teachers with regards to the concepts of speed, sound, condensation and germination. It also sought go determine whether any significant differences existed between the level of the teachers' scientific understandings across gender, ethnic groups, academic and professional qualifications, science-teaching experience and attitudes towards science. The population of this study comprised all practicing primary school science teachers in the district of Kuching, Sarawak.